The Curriculum Reform of Design Education Based on the Orientation of Positive Psychology - Wu, Yi; Kyungsun, Kymn (Frontiers in Psychology, 2022)
In the process of China’s rapid development, the society has higher and higher requirements for educational reform. Different from other basic disciplines, design emphasizes practicality, which requires that in the process of design education reform, more attention should be paid to the stimulation of students’ subjective initiative and the improvement of students’ ability to solve problems in the face of setbacks. This paper methodically expounds on a more scientific manner of curriculum reform fit for China’s educational system, based on positive psychology and consideration of grit. It performs research and analysis on the design education curriculum reform on the basis of positive psychology through field research, logical analysis, and other research methodologies. Designing education curriculum reform based on positive psychology orientation is more feasible than standard education curriculum reform and the role of grit in taking part in the educational curriculum reform oriented to positive psychology is considerably higher than that in the conventional educational curriculum reform, according to experimental study.